Clinical characteristics and genetic analyses of 187 patients with undefined autoinflammatory diseases. Issue 10 (October 2019) - Ter Haar, Nienke M; Eijkelboom, Charlotte; Cantarini, Luca; Papa, Riccardo; Brogan, Paul A; Kone-Paut, Isabelle; Modesto, Consuelo; Hofer, Michael; Iagaru, Nicolae; Fingerhutová, Sárka; Insalaco, Antonella; Licciardi, Francesco; et al.
Abstract : Objectives: To describe the clinical characteristics, treatment response and genetic findings in a large cohort of patients with undefined systemic autoinflammatory diseases (SAIDs). Methods: Clinical and genetic data from patients with undefined SAIDs were extracted from the Eurofever registry, an international web-based registry that retrospectively collects clinical information on patients with autoinflammatory diseases. Results: This study included 187 patients. Seven patients had a chronic disease course, 180 patients had a recurrent disease course. The median age at disease onset was 4.3 years. Patients had a median of 12 episodes per year, with a median duration of 4 days. Most commonly reported symptoms were arthralgia (n=113), myalgia (n=86), abdominal pain (n=89), fatigue (n=111), malaise (n=104) and mucocutaneous manifestations (n=128). In 24 patients, relatives were affected as well. In 15 patients, genetic variants were found in autoinflammatory genes. Patients with genetic variants more often had affected relatives compared with patients without genetic variants (p=0.005). Most patients responded well to non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, colchicine and anakinra. Complete remission was rarely achieved with NSAIDs alone. Notable patterns were found in patients with distinctive symptoms. Patients with pericarditis (n=11) were older at disease onset (33.8 years) and had fewer episodes per year (3.0/year) compared with other patients. Patients with an intellectual impairment (n=8) were younger at disease onset (2.2 years) and often had relatives affected (28.6%). Conclusion: This study describes the clinical characteristics of a large cohort of patients with undefined SAIDs. Among these, patients with pericarditis and intellectual impairment appear to comprise distinct subsets.